A dual CoNi MOF nanosheet/nanotube assembled on carbon cloth for high performance hybrid supercapacitors. (10th May 2020) - Xu, Shusheng; Liu, Ruiqi; Shi, Xuerong; Ma, Yujie; Hong, Min; Chen, Xinwei; Wang, Tao; Li, Fangjie; Hu, Nantao; Yang, Zhi
Abstract: Layered-structure MOF is a promising material for electrochemical energy storage applications. However, low conductivity hinders their electrochemical performance. Herein, a hierarchical layered-structure CoNi-MOF with ultrathin nanosheets and nanotube arrays are directly grown on carbon cloth (CC) with Co(OH)2 as both template and Co source. The synthesized CC/CoNi-MOF shows high areal capacity of 1.01 C cm −2 at 2 mA cm −2, while keeps 61.4% capacity retention at 15 mA cm −2 . A hybrid supercapacitor is successfully fabricated with CC/CoNi-MOF as positive electrode and reduced graphene oxide-carbon nanotube as negative electrode, possessing a maximum areal capacitance of 846 mF cm −2 at 1 mA cm −2, a high energy density of 55.5 Wh kg −1 at 175.5 W kg −1, and excellent cycling stability (96.5% after 10000 cycles). This work may pave a new way for designing MOF based materials with similar structure for high performance supercapacitors. Graphical abstract: A dual CoNi-MOF nanosheet/nanotube assembled on carbon cloth for high energy supercapacitors. Image 1 Highlights: A dual CoNi MOF nanosheet/nanotube was assembled on carbon cloth. Co(OH)2 was used as both template and Co source. The synthesized CC/CoNi-MOF shows high areal capacity of 1.01 C cm −2 . Our hybrid supercapacitor exhibited a high energy density of 55.5 Wh kg −1 and excellent cycle stability.